Changes in T2 Relaxation Time Mapping of Intervertebral Discs Adjacent to Vertebrae after Kyphoplasty Correlate with the Physical Clinical Outcome of Patients - Lisa C. Wegener; Felix Werner; Arnd Kleyer; David Simon; Michael Uder; Rolf Janka; Siegfried Trattnig; Goetz H. Welsch; Milena L. Pachowsky (Diagnostics, 2022)
(1) Background: To assess whether clinical outcomes correlate with tissue changes in the intervertebral discs (IVDs) after kyphoplasty as treatment for vertebral fractures, quantitative MRI was applied. (2) Methods: Quantitative T2 mapping acquired in a 3 T MRI scanner of the thoracolumbar spine was performed in 20 patients two years after kyphoplasty. The IVDs adjacent and nonadjacent to the treated vertebrae were divided into six regions of interest (ROI), which were further categorised into inner (ROI 2–5) and outer (ROI 1 and 6) parts of the IVDs, and the T2 values were analysed. T2 values of adjacent discs were correlated with the items of questionnaires evaluating the clinical outcome (i.e., 36-Item Short Form Survey). (3) Results: Lower T2 values in adjacent IVDs correlated with poorer physical outcome two years after kyphoplasty. The inner part of the IVDs adjacent to treated vertebrae showed statistically significant lower T2 values in segments L2/L3 and L3/L4 compared to nonadjacent ones. Patients with lower T2 values showed more pain and physical limitations in everyday life. (4) Conclusions: Quantitative T2 mapping can detect IVD degeneration in patients after kyphoplasty and correlates with the physical outcome. This technique could help to gain better insights into alterations in tissue composition following kyphoplasty and the consequences for the patients’ quality of life.